Penerapan Akuntansi Pada Umkm Level Up Bistro Kota Gorontalo - Mattoasi Mattoasi; Hapsawati Taan; Siti Verogita Ahmad (Journal Of Business, Finance, and Economics (JBFE), 2022)
This study aims to determine the Application of Accounting in Micro, Small and        Medium Enterprises at the Level Up Bistro in Gorontalo City. The problem discussed in       This study is whether the application of accounting in MSME Level Up Bistro is in      accordance with SAK-EMKM.This study uses a qualitative approach. Data was collected using the interview method with the owner and employees of Level Up Bistro and documentation.The results of this study indicate that Level Up Bistro SMEs apply accounting by changing the recording model to simple and not following the Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). From the results of the interviews conducted, it was shown that the recording carried out at Level Up Bistro was only limited to recording income and expenses.